KAJIAN USAHATANI JAGUNG DI DESA PASI MALI KECAMATAN WOYLA BARAT KABUPATEN ACEH BARAT - Devi Agustia; Dara Angreka Soufyan (Jurnal Bisnis Tani, 2019)
One of the food commodities that has prospect to developed in order to meet the need of domestic and international markerts is corn. Corn has prospect if it is managed intensive, where corn is a food crop whose use is relatively broad, namely for the food, chemical and feed industries. The corn farming activities carried out by the respondent farmer are stiil small scale, the purpose of the aims study to examine the characteristics of farming and pattern in the village of Pasi Mali in particular is the characteristics of farming identify farming and income of corn farming. The analysis used is descriptive and quantitative. Quantitative analysis to calculate farm income with cost a cost structure approach. The analysis result that corn farming is feasible to cultivated.